PERFIL GERENCIAL DOS REITORES DE UNIVERSIDADES PÚBLICAS FEDERAIS: O FRÁGIL EQUILÍBRIO DE COMPETÊNCIAS ACADÊMICAS E GERENCIAIS - Quintiere, Rita de Cássia Borges de Campos (2012)
The management of academic institutions requires the implementation of strategic planning and constant review to enable these organisations to provide high quality services to society. This planning should be designed and implemented by administrators with the necessary competencies for this task. Nevertheless, it is often the case, even though a rector is seemingly prepared for the position be it for his/her academic qualifications or professional experience, this position does not require management qualifications. In this context, this dissertation aims at assessing, from the point of view of rectors from Rio de Janeiro state universities, how these administrators acquire the competencies or should acquire the competencies that would provide them with a managerial profile. The theoretical framework is based on the work of Le Boterf (1995/2007), Zarifian (2001), Fleury & Fleury (2001), Kilimnik et al. (2004), Carvalho et al (2009), Amaral (2006), Oliveira, Sant Anna e Vaz (2010), and Spendlov (2007), who understand competencies as a set of knowledge that move and transform social and work relations. More specifically, the discourse of the rectors interviewed was assessed using the three dimensions proposed by Le Boterf (1995/2007), namely: a) personal trajectories, b) education, and c) professional experience. These theoretical categories were tested using in-depth interviews and the methods of content analysis proposed by Bardin (2009). A survey (hereafter named Pinga-fogo ) was also applied to directors at the Universidade Federal Fluminense. Results show that the majority of rectors develop their managerial competencies on the job, through experiences as well as challenges and opportunities identified by the manager in the institutional context.